SUSTAINABLE CULTURE AND ENERGY USE IN HOTEL RESORTS - Milan Ambrož; Božidar Veljković (Journal of Energy Technology, 2024)
The aim of this study was to investigate the mission of hotels and hotels resorts regarding the development of sustainable tourism. The organizational behaviour regarding the energy consumptions of thirteen hotels from Posavje, and the 47 employees and managers from these hotels participated was examined. They were questioned with a Likert type questionnaire about the factors that influence their attitudes toward sustainable energy consumption in hotel. Empirical findings of the study show that long-term vision, long-term strategy-oriented behaviour, consensus seeking about energy consumption, and employee involvement are the most important factors of sustainable behaviour. The study opens a new perspective in the research of the emergence of ‘green’ culture based on energy consumption strategy, innovative governance of waste and waste water and its recycle fire and accident protection, transforming solid waste into new energy, the use of new technology, and the integration of the infrastructure of tourism systems.